In the skin lesions of patients with mycosis fungoides, the number of MRGPRX2-expressing cells is increased and correlates with mast cell numbers - Hu, Man; Pyatilova, Polina; Altrichter, Sabine; Sheng, Caibin; Liu, Nian; Terhorst-Molawi, Dorothea; Lohse, Katharina; Ginter, Katharina; Puhl, Viktoria; Maurer, Marcus; Metz, Martin; Kolkhir, Pavel (Frontiers in Immunology, 2023)
Background: Mycosis fungoides (MF) is an indolent T-cell lymphoma that mainly affects the skin and presents with itch in more than half of the patients. Recently, the expression of Mas-related G protein-coupled receptor X2 (MRGPRX2), a receptor of mast cell (MC) responsible for the IgE-independent non-histaminergic itch, has been shown in lesional skin of patients with pruritic skin diseases, including chronic urticaria, prurigo, and mastocytosis. As of yet, limited knowledge exists regarding the MRGPRX2 expression in the skin of patients with MF. Objectives: To investigate the number of MRGPRX2-expressing (MRGPRX2+) cells in the skin of MF patients and its correlation with clinical and laboratory characteristics of the disease. Methods: MRGPRX2 was analyzed in lesional and non-lesional skin of MF patients and healthy skin by immunohistochemistry. Co-localization of MRGPRX2 with the MC marker tryptase was assessed by immunofluorescence. Public single-cell RNAseq (scRNAseq) data was reanalyzed to identify the MRGPRX2 expression on the distinct cell types. Results: In the lesional skin of MF patients, MRGPRX2+ cells number was higher than in non-lesional skin and healthy control skin (mean:15.12 vs. 6.84 vs. 5.51 cells/mm 2 , p=0.04), and correlated with MC numbers (r=0.73, p=0.02). MC was the primary cell type expressing MRGPRX2 in MF patients. The ratio of MRGPRX2+ MCs to MRGPRX2+ cells in lesional and non-lesional skin correlated with the severity of disease (r=0.71, p=0.02 and r=0.67, p=0.03, respectively). Conclusions: Our findings point to the role of MRGPRX2 and MC in the pathogenesis of MF that should be investigated in further studies.